In situ investigation of MgO nanocube deformation at room temperature. (March 2015) - Issa, I.; Amodeo, J.; Réthoré, J.; Joly-Pottuz, L.; Esnouf, C.; Morthomas, J.; Perez, M.; Chevalier, J.; Masenelli-Varlot, K.
Abstract: The mechanical behavior of 〈1 0 0〉-oriented MgO nanocubes is investigated using in situ transmission electron microscopy (TEM) compression tests at room temperature and molecular dynamics simulations. Experiments show high strength and ductility, in addition to specific deformation mechanisms interpreted by the simulation. The nucleation and the propagation of 1/2〈1 1 0〉1 1 0 dislocations are at the onset of the plastic deformation. The different deformation processes as well as the possible formation of a dislocation network during compression are discussed.